Reversible response of a magnetic surface acoustic wave device with perpendicular magnetization. (26th May 2020) - Polewczyk, Vincent; Lacour, Daniel; Dumesnil, Karine; Mjahed, Hamid; Petit-Watelot, Sébastien; Montaigne, François; Elmazria, Omar; Hehn, Michel
Abstract: Magnetic surface acoustic wave (MSAW) devices combine a magnetostrictive material with a piezoelectric material to enable the sensing/measurement of magnetic fields by electrically generated SAWs. In such systems, the response is strongly dependent on the field direction with respect to the magnetic anisotropy of the magnetic material, which could give rise to detrimental hysteretic behaviour. The challenge in the current study is to control the shape of MSAW responses and remove the hysteresis in the magneto-acoustic response. We report especially on the magnetic response of a MSAW device with perpendicular magnetic anisotropy, rarely reported in literature. On the basis of the MSAW response with in-plane magnetic anisotropy studied previously, the MSAW signal with out-of-plane magnetization could be understood for all the field configurations. The final response is hysteresis free, which is suitable for interrogation of out of the plane magnetic fields. Such a technology could therefore complete the 'in-plane' sensing technology to build up 3D sensors.